TINDAK PIDANA MENYURUH MEMASUKKAN KETERANGAN PALSU DALAM AKTE OTENTIK (STUDI PUTUSAN NOMOR : 1545/PID.B/2012 PN. MEDAN. JO PUTUSAN NOMOR :39/PID/2013/PT.MEDAN.) - Themis Simaremare; Muhammad Hamdan; Mahmud Mulyadi; Jelly Leviza (USU LAW JOURNAL, 2015)
ABSTRACT Article 266th -  first paragraph of the Criminal Code, about "people who were told to do". Case on 4th March, 2008 at Tulung Agung office, the  witness, Eveline Sago bought land  from Octo Berman Simanjuntak in Mandailing Natal, North Sumatra at  price USD. 6,000,000,000. The  High Court of  Medan  convict  the defendant to imprisonment for 1 (one) year and 6 (six) months confinement, specify the period of detention has been done by the defendant deducted entirely of imprisonment imposed, ordered defendant was arrested to jail break for eight months, and ordered the evidence to be returned to the Octo Berman Simanjuntak. This research also discuss about normative law ( normative juridical). And  the  characteristic is perspective analysis with “statute” and “analytical” approaches  to analysis  the  case. The results of this research contains : (a) The wearing of act (b) Fake letter and forged letters, (c) Using of subjective element (d) Actions (e) Objects (f) Authentic deed (g) the truth (h) cause harm ( Article 263rd and 266th ). Keywords: Crime, Entering False Information, Authentic Deed